Comparative assessment of joint water development initiatives in the Jordan River Basin. Issue 1 (2nd January 2017) - Quba'a, Rola; El-Fadel, Mutasem; Abou Najm, Majdi; Alameddine, Ibrahim
ABSTRACT: This paper presents a comparative assessment of developmental initiatives to increase regional water supply in the Jordan River Basin using a Multi Criteria Decision Analysis technique with sensitivity analysis on criteria weights. The results indicate that the Red Sea–Dead Sea Conveyance (RSDSC) constitutes an optimal option within the context of alleviating water shortage and promoting regional cooperation. While a surface water pipeline from Turkey emerges as an attractive option when the quantity of delivered water is emphasized, the potential for out of basin water transfers are becoming increasingly less desirable with population growth, political turmoil in the region, development, and climate change challenges.